Taxonomy of Financial Reporting in the Context of Digitalization of the Economy: Domestic and International Analysis Scientific Research - Vysochan, Oleh S.; Hyk, Vasyl; Mykytyuk, Nataliya; Vysochan, Olha O. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
A clear manifestation of the technological revolution 4.0 in the context of digitalization of the economy is the use of digital, electronic, or IT-oriented versions of financial reporting. Today, the harmonization of national accounting systems and the formation of financial statements around the world is carried out through the implementation of International Financial Reporting Standards by moving to the preparation of financial statements in a single electronic format – eXtensible Business Reporting Language (XBRL). The introduction of a new financial reporting system in XBRL format requires appropriate understanding and some practical adaptation. At the same time, the study of the use of the concept of “taxonomy financial reporting” in scientific works remains insufficiently developed. The article aims to study the quantitative and qualitative structure of the documentary flow of scientific periodicals on the keywords “taxonomy financial reporting”. The method of bibliometric analysis was used to conduct the study. The source of the bibliometric analysis of the documentary flow of scientific periodicals are publications from the scientometric database Scopus in the period between 2001-2021. As a result of the selection, data were obtained on scientific articles that were exported for processing into the computer program R (bibliometrics package). According to the results of quantitative analysis, 156 publications were received, the vast majority of which were scientific articles. It was found that the main areas of research on the taxonomy of financial reporting are: taxonomies, XBRL, financial reporting, and administrative data processing. The largest clusters appear around these keywords. It has been established that scientific cooperation on this topic is becoming closer, which contributes to the formation of geographical clusters, the three largest of which are united around the United States, Italy and the United Kingdom.